On the New RILEM Technical Committee TC APD: Alternative Paving Materials – Design and Performance - Augusto Cannone Falchetto; Fan Yin; Maria Chiara Cavalli; Salvatore Mangiafico; Krishna Prapoorna Biligiri; Justine Cantot; Punyaslok Rath; Avishreshth Singh; Michael Elwardany; Di Wang; Chen Chen; James Grenfell; et al. (RILEM Technical Letters)
This paper introduces the new RILEM Technical Committee on Alternative Paving Materials – Design and Performance (TC APD), which builds upon the foundational efforts of the former TC 279-WMR focused on the Valorisation of Waste and Secondary Materials for Roads. The TC APD aims to advance the understanding of alternative paving materials, emphasizing their design and performance as essential components of road composites. The committee addresses three areas of investigation, each dedicated to examining the current technological state of the art, the design process and the field performance of composites incorporating alternative paving materials. The manuscript provides a comprehensive overview of the TC's background, outlines the research objectives and activities proposed, and discusses the committee's position within RILEM and the broader research community. Additionally, it details the anticipated outcomes and the potential impact of the committee's work on advancing the field of sustainable road construction.